Correction to: Assessing the Quality of Incident Investigationsand its Effect on Safety Performance: a Studyof the Ghanaian Mining Industry Mining, Metallurgy and Exploration - Eric Stemn; Maureen E. Hassall; Carmel Bofinger; David Cliff (Society for Mining, Metallurgy & Exploration)
e Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.